EXPLORING THE PERSUASIVE DESIGN ELEMENTS OF INSTAGRAM - Fathima Musfira Ameer; Nurulhuda Ibrahim; Harryizman Harun, (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
Existing literature has established that social media can be highly persuasive on a broader scale, yet comprehensive evaluation of persuasive strategies on Instagram remains scarce despite its widespread usage. Instagram, a globally popular social networking platform, lacks thorough academic examination regarding its persuasive technological strategies despite its significant impact on user behaviour and interaction patterns is already realised. The platform's emphasis on visual content, interactive features, and evolving engagement tools presents a unique landscape for studying persuasive strategies. This study aims to fill this gap by assessing the integration of persuasive technological strategies within Instagram, focusing on behaviour change and user motivation. Employing the 'Persuasive Systems Design (PSD)' framework, widely recognized for developing and evaluating persuasive systems, this study dissects persuasive elements in Instagram. The evaluation reveals an effective utilization of persuasive techniques to engage and captivate users on Instagram. This evaluation not only contributes academically but also holds implications for industrial practices, offering insights into how persuasive designs influence user behaviour on a highly influential social media platform.